2022
DOI: 10.30935/mjosbr/11820
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Extended Advertising Value Model: A Case of TikTok Short Video Ads

Abstract: Nowadays, TikTok social media has rapidly developed which creates an opportunity for marketers to grab customers' attention by displaying short video ads. For this reason, knowledge of the factors that can influence customer purchase intentions is needed so that marketing strategies can work effectively. This study aims to investigate the effects of the entertainment, informativeness, credibility, irritation, personalization, and interactivity elements of TikTok short video ads on purchase intention through ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This shows that perceived enjoyment is one of the important elements for TikTok users. Dwinanda et al (2022) found a positive relationship between entertainment and the formation of perceived advertising value because the respondents felt entertained and enjoyed watching TikTok video ads. The content displayed on TikTok ads is generally funny or involves dancing, acting, and lip-syncing, which meets the interests of Gen Y and Gen Z (Dwinanda et al, 2022).…”
Section: Perceived Enjoyment and Urge To Purchase Impulsivelymentioning
confidence: 89%
See 1 more Smart Citation
“…This shows that perceived enjoyment is one of the important elements for TikTok users. Dwinanda et al (2022) found a positive relationship between entertainment and the formation of perceived advertising value because the respondents felt entertained and enjoyed watching TikTok video ads. The content displayed on TikTok ads is generally funny or involves dancing, acting, and lip-syncing, which meets the interests of Gen Y and Gen Z (Dwinanda et al, 2022).…”
Section: Perceived Enjoyment and Urge To Purchase Impulsivelymentioning
confidence: 89%
“…Li et al (2021) investigated the purchase intention of China residents in Changsha through TikTok; their results revealed that perceived media richness was the most influencing factor. Dwinanda et al (2022) studied the influences of TikTok advertising elements and attitudes on consumers' purchase intention in Indonesia. Research that focuses on TikTok and impulsive purchase behaviour is even dearth.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that there is a positive correlation between entertainment and the development of perceived advertising value. The respondents in the study reported feeling entertained and enjoying viewing TikTok video ads (Dwinanda et al, 2022). H2: Video quality has a significant relationship with students' purchase intention towards fashion products.…”
Section: Literature Reviewmentioning
confidence: 94%
“…This variable holds significance as consumer perceptions of price fairness play a crucial role in shaping their intentions to make purchases (En & Balakrishnan, 2022). In a prior study conducted by Dwinanda et al (2022) in Indonesia, it was revealed that consumers' perceived price fairness had a notable positive impact on their intentions to make purchases. Derived from this earlier research, the hypothesis suggests that an enhanced perception of price fairness will result in increased purchase intentions among consumers…”
Section: Perceived Price Fairnessmentioning
confidence: 99%
“…The richer the media, the more DOI: 10.47191/ijcsrr/V7-i3-57, Impact Factor: to develop a strong understanding and appreciation of the products, potentially leading to higher purchase intentions.Perceived Price Fairness: This variable relates to how consumers perceive the fairness of prices on Shopee's live streaming service. If consumers deem the prices as reasonable and justifiable, they are more likely to proceed with a purchase(Dwinanda et al, 2022;En & Balakrishnan, 2022). Fair pricing strategies can enhance consumer trust and loyalty, making it a critical factor in the decision-making process.Electronic Word of Mouth (eWOM): eWOM is included due to its significant influence on consumers' perceptions and buying decisions.…”
mentioning
confidence: 99%